Artificial Intelligence in Education: Can AI Improve Teacher Performance or Will It Replace Them? - Nida Ul Hasanah; Amar Ali Aulia; Muhammad Azhar Abdillah; Novel Daud Poedjiono (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The rapid advancement of artificial intelligence (AI) has transformed educational practices and generated critical debates regarding whether AI enhances teacher performance or threatens the continuity of the teaching profession. This study aims to examine the role of AI in education by analyzing its contributions, limitations, and potential relationship with human teachers. Employing a non-empirical qualitative literature review approach, this research synthesizes international scholarly publications concerning generative AI, personalized learning, classroom management, human-AI collaboration, and the human dimensions of teaching. The findings indicate that AI significantly improves educational efficiency through automation, adaptive learning support, and data-driven instructional assistance. Nevertheless, AI remains limited in performing affective, ethical, and relational functions that constitute essential components of effective teaching. The study concludes that AI is unlikely to replace teachers entirely but will reshape their professional roles through collaborative human-AI models. This research contributes to the theoretical development of hybrid intelligence perspectives in education and provides a comprehensive understanding of technology integration that preserves the centrality of human pedagogical expertise.